Pola Kunjungan Pusat Perbelanjaan Di Pusat Kota Semarang (Studi Kasus: DP Mall) - Diva Khansa Gustanti; Yudi Basuki (Jurusan Perencanaan Wilayah dan Kota, 2021)
Shopping center, as one of the land uses in trade and service activities, has a high intensity of travel demand to attract movement and cause travel attraction. Duta Pertiwi Mall is a shopping center that located in the center of Semarang City and has the potential to attract high numbers of visitors. This study aims to understand the relationship between travel attraction and the characteristics of trade and service areas through analysis of movement patterns at Duta Pertiwi Mall as a shopping center in the city center. The research method used is the analysis of movement patterns. The data that will be used in this research is the distribution of visitors from Duta Pertiwi Mall. The output produced in this study is Duta Pertiwi Mall has a regional service scale with visitors from out of town up to 14% and local visitors 86%.